USP22 is a positive regulator of NFATc2 on promoting IL2 expression. Issue 6 (20th February 2014) - Gao, Yayi; Lin, Fang; Xu, Peng; Nie, Jia; Chen, Zuojia; Su, Jinsong; Tang, Jiayou; Wu, Qingsi; Li, Yangyang; Guo, Zhixiang; Gao, Zhimei; Li, Dan; et al.
Abstract : Nuclear factor of activated T cells (NFAT) is an important regulator of T cell activation. However, the molecular mechanism whereby NFATc2 regulates IL2 transcription is not fully understood. In this study, we showed that ubiquitin‐specific protease 22 (USP22), known as a cancer stem cell marker, specifically interacted with and deubiquitinated NFATc2. USP22 stabilized NFATc2 protein levels, which required its deubiquitinase activity. Consistent with these observations, depletion of USP22 in T cells reduced the expression of IL2, which is a cytokine that signifies T effector cell activation. Our findings thus unveil a previously uncharacterized positive regulator of NFATc2, suggesting that targeting the deubiquitinase activity of USP22 could have therapeutic benefit to control IL2 expression and T cell function. Abstract : USP22 interacts with NFATc2. USP22 deubiquitinates and stabilizes NFATc2. USP22 is required for NFATc2‐mediated upregulation of IL2.